Optimasi rute distribusi gas LPG 3 kg menggunakan metode tabu search pada PT. SPI - Tarnoto Tarnoto; Wahyudin Wahyudin; Risma Fitriani (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2021)
PT. SPI is one of the agents of 3 kg LPG gas in the Karawang area, where there are problems in the process of distributing 3 kg LPG gas, because the route chosen for delivery is based on the intuitiveness of the driver who carries out the distribution process. PT. SPI has 11 vehicles where there are differences in vehicle capacity, therefore the problem of PT. SPI is a type of Heterogeneous Fleet Vehicle Routing Problem. This study aims to determine the optimal distribution route, calculate the distribution costs required by PT. SPI to the base and compare the company's existing route with the proposed route that is formed based on the total distance traveled and the costs to be incurred. The method used in this research is the method Clarke and Wright saving as the initial solution assignment which is then optimized by the method Tabu search. The results obtained in this study are the method Tabu search can form a route that is close to optimal with a total distance of 1323.4 kilometers with the search process using a maximum of 60 iterations can reduce the total distance traveled on Monday to Saturday, the difference from the total existing mileage with the proposed route is 141.2 kilometers with a percentage of the decrease in the existing total mileage with the total proposed mileage as a whole is 9.6% In addition, it can provide a total distribution cost of Rp. 24,015,811,- /week, and the difference between the existing total distribution costs and the proposed distribution costs is Rp. 1,758,994 and can be presented as a decrease in total distribution costs of 6.8%.